A Pragmatic Study to Evaluate the Use of a Rapid Diagnostic Test to Detect Group A Streptococcal Pharyngitis in Children With the Aim of Reducing Antibiotic Use in a UK Emergency Department. Issue 5 (May 2021) - Bird, Chris; Winzor, Gemma; Lemon, Katherine; Moffat, Alasdair; Newton, Tina; Gray, Jim
Abstract : Objective: Sore throat is a common presentation to the children's emergency department (ED), and many patients are likely prescribed antibiotics unnecessarily. We aimed to reduce antibiotic prescribing for sore throat in our UK ED through use of an established scoring system combined with a rapid diagnostic test (RDT) to detect group A streptococcal (GAS) pharyngitis. Methods: AB single-subject and diagnostic accuracy studies were used to measure both antibiotic prescribing rates over time and the performance of the McIsaac clinical score combined with RDT to screen for and treat GAS pharyngitis. All children between the age of 6 months and 16 years with symptoms of sore throat were eligible for inclusion. The study adhered to SQUIRE guidelines. Results: During 2014 and 2016, antibiotic prescribing rates for 210 children at baseline (median age, 3 years) and 395 children during the intervention (median age, 2 years) were assessed. The baseline prescribing rate was 79%, whereas rates after intervention were 24% and 27%, respectively. The RDT had an acceptable false-negative rate of 7.9%, poor sensitivity of 64.3%, and a negative predictive value of 92.1% when compared with conventional throat culture. A McIsaac score of 3 or more had good sensitivity (92.11%) but very low specificity (12.62%) for predicting GAS infection. Conclusions: Despite poor RDT sensitivity and the McIsaac score's poor specificity in children, their use in combination decreased antibiotic prescribing rates in a children's ED setting. Abstract : Supplemental digital content is available in the text.